Perinatal Penicillin Exposure Affects Cortical Development and Sensory Processing - Perna, James; Lu, Ju; Mullen, Brian; Liu, Taohui; Tjia, Michelle; Weiser, Sydney; Ackman, James; Zuo, Yi (Frontiers in Molecular Neuroscience, 2021)
The prevalent use of antibiotics in pregnant women and neonates raises concerns about long-term risks for children’s health, but their effects on the central nervous system is not well understood. We studied the effects of perinatal penicillin exposure (PPE) on brain structure and function in mice with a therapeutically relevant regimen. We used a battery of behavioral tests to evaluate anxiety, working memory, and sensory processing, and immunohistochemistry to quantify changes in parvalbumin-expressing inhibitory interneurons (PV+ INs), perineuronal nets (PNNs), as well as microglia density and morphology. In addition, we performed mesoscale calcium imaging to study neural activity and functional connectivity across cortical regions, and two-photon imaging to monitor dendritic spine and microglial dynamics. We found that adolescent PPE mice have abnormal sensory processing, including impaired texture discrimination and altered prepulse inhibition. Such behavioral changes are associated with increased spontaneous neural activities in various cortical regions, and delayed maturation of PV+ INs in the somatosensory cortex. Furthermore, adolescent PPE mice have elevated elimination of dendritic spines on the apical dendrites of layer 5 pyramidal neurons, as well as increased ramifications and spatial coverage of cortical microglia. Finally, while synaptic defects are transient during adolescence, behavioral abnormalities persist into adulthood. Our study demonstrates that early-life exposure to antibiotics affects cortical development, leaving a lasting effect on brain functions.